Chemical composition and photoprotective potential of aqueous extract from Casearia sylvestris var. lingua (Cambess.) Eichler leaves - Cardoso, Claudia Andrea Lima; Aguayo de Castro, Thiago Luis; Duarte Goneli, André Luís; Verdan, Maria Helena (Orbital: The Electronic Journal of Chemistry, 2022)
Casearia sylvestris var. lingua (Cambess.) Eichler is widely used in traditional medicine to treat diseases. Simultaneously, the growing search for phytocosmetics has culminated in the exploration of plant extracts. In this context, the aim of this study was to obtain the chemical composition and antioxidant and photoprotective potential of the infusion of C. sylvestris var. lingua leaves. The techniques of UV/Vis spectroscopy, gas chromatography with mass spectrometry detector (GC-MS) and liquid chromatography with diode array detector (LC-DAD) were used to get the results. The total phenolic content in the infusion of leaves from C. sylvestris var. lingua was 101.57 mg GAE g-1, flavonoids 50.37 mg RE g-1 and tannins 1.12 mg TAE g-1. Quercetin, ferulic acid, gallic acid, ellagic acid, caffeic acid, β-sitosterol, lupeol, lupeol acetate, stigmasterol and campesterol were identified and quantified in the samples. The infusion of C. sylvestris var. lingua leaves has potential for application in phytocosmetics and sunscreens, with a sun protection factor of 8.65 ± 0.45, a UVA/UVB ratio of 1.16 and a critical wavelength of 373.